Pengaruh Work-Family Conflict Dan Stres Kerja Terhadap Kinerja Karyawan Di Daima Hotel Padang - Anjelly Ramadhani Ismu; Mellyna Eka Yan Fitri (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to examine the effect of Work-Family Conflict and job stress on employee performance at Daima Hotel Padang. The background of this research arises from the phenomenon that employees face high job demands on one side and family responsibilities on the other, which can create role conflicts and increase job stress levels.This research applied a quantitative approach with an associative method. The population in this study consisted of all employees of Daima Hotel Padang, totaling 63 people, using a saturated sampling technique. The research instrument was a questionnaire with a Likert scale. The validity and reliability tests were conducted to ensure the quality of the instrument, while the data analysis used multiple linear regression with the help of SPSS.The results showed that Work-Family Conflict has a positive but not significant effect on employee performance. Meanwhile, job stress has a positive and significant effect on employee performance. Simultaneously, Work-Family Conflict and job stress significantly affect employee performance. Among these variables, job stress was found to be the most dominant factor influencing employee performance.Based on these findings, the management of Daima Hotel Padang is expected to pay more attention to managing employees’ job stress and support the balance between work and family roles so that employee performance can be improved optimally.